Experimental study on mechanical behavior of silty-fine sand reinforced by a new type of permeable polymer material under dry-wet cycles - Yuke Wang; Liao Zhang; Xinming Qu; Mengcheng Liu; Yanhui Zhong; Bei Zhang (Soils and Foundations)
Silty-fine sand in the Yellow River floodplain is prone to geological hazards such as collapse, subsidence, gushing water, and sand routing triggered by groundwater seepage. As a new type of grouting material, permeable polymer is effective for solving silty-fine sand geologic hazards. With the rise and fall of the water table, capillary water, and transpiration, the reinforced silty-fine sand will be subjected to dry-wet cycles. Investigating the strength loss mechanism of specimens reinforced with permeable polymer during dry-wet cycles is essential for mitigating silty-fine sand geological hazards. The strength characteristics of permeable polymer grout-reinforced silty-fine sand specimens under dry-wet cycles and its extreme case (long-time immersion) were analyzed from macro and micro perspectives employing unconfined compressive strength (UCS) test and scanning electron microscope (SEM). The functional calculation model between the specimens and the initial grouting conditions under dry-wet cycles was constructed, and the main influencing factors of the UCS loss of the specimens were obtained. After permeable polymer grouting, the porosity of silty-fine sand is reduced effectively and the porous structure is changed. The grouted specimens maintain structural integrity and demonstrate excellent water stability even after dry-wet cycles.